Supply Chain Finance Analysis Towards Corporate Performance in PT ABC - Purnomo, Orieza Alif Putra; Handayati, Yuanita (Journal of Business and Management, 2015)
Abstract. PT.ABC is a steel fabricator company with many projects and experience in steel industry and infrastructure. As one of the manufacturing company, PT.ABC is relaying their operational activities through supply chain management. Supply chain management is one of strategic decision of a business. Supply chain management is also a network of organization that includes supplier, manufacturers, distributors, retailers, and customers. Focus of supply chain management is took place in the customers side, the primary purpose of the existence of supply chain management is to satisfy the customer needs, alongside the process of gaining profit. In order to maximize the operational activity of supply chain management, financial side is taking support in background. To support supply chain management there are several tools that also taking advantage in the financial side, one of them is supply chain finance (SCF). Supply chain finance is an alternative funding consists of three different parties’ there are financial institution (bank), buyer, and supplier. SCF form a different way of funding that affected company’s financial performance to leading into operational performance. The purpose of this study is to identify impact from applying SCF program toward four different indicators as the working investment, account payable desk on hand, the cost of goods sold, and current ratio specifically seen from buyer’s perspective. To analyze the findings, a quantitative descriptive analysis employed. The result of this study could use to evaluate operational performance through financial performance in the company. The result is important because it will explain the improvement of performance and the impact of applying SCF program based on four indicators. By knowing those indicators, it can help PT.ABC to decide whether to use this program or not in the next year business activity. Keywords : Supply Chain Finance, Buyer perspective, Corporate performance, Steel fabricator, Manufacturing.